Eyewear Shop Management System - Ng, Jun Hui; Marjudi, Suziyanti (Applied Information Technology And Computer Science, 2023)
A report by the World Health Organization states that globally, at least 2.2 billion people have near or distance vision impairments. One of the solutions in the treatment of refractive errors and avoiding a continuous increase in vision is by wearing glasses. In current, some optical stores still maintain manual sales placement and information management. Sometimes this can generate issues such as multiple data inputs or migrations from handwritten records to Excel files, which can lead to errors and be time-consuming. Therefore, the Eyewear Shop Management System will be developed to replace or provide stores with an alternative to manual operation. The main role of this system will assist the users’ in selling the glasses or contact lens to the customer by choosing the lenses and frames, or contact lens that have been registered in the inventory. In addition, this Web-based System will develop based on the structured approach and Waterfall model, and through the PHP programming language, Visual Studio Code software, and MySQL as the database to develop. As a result of this project, the creation of this system will allow workers of the optical store to sell glasses and contact lens to customers and manage inventory, and view sales records.